Horses and Risk - Thompson, Kirrilly (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The risk of physical accident or injury to humans from horses is well understood. Now, there is increasing awareness of negative impacts on the physical and mental wellbeing of horses from living in fundamentally human environments and being subject to human management regimes. The 17 articles in this collection describe horse-related risks to humans and human-related risks to horses across a range of equestrian disciplines, sectors and activities. Not only do the authors take detailed approaches towards describing and calculating risk, they suggest solutions-focussed interventions for reducing the consequence and likelihood of harm to horses and humans in their relations with one another. Together, these important articles provide strategies for maximising the mutual benefits of humans and horses in each other's lives. By considering human, animal and environmental aspects of horse-related risk, this collection provides a foundation for the development of an 'Equestrian One Health' framework to underpin future research into horse-related risks.